1995
DOI: 10.1016/s1078-5884(05)80010-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spinal cord stimulation (SCS) in patients with inoperable severe lower limb ischaemia: A prospective randomised controlled study

Abstract: SCS provided long-term pain relief but limb salvage at 18 months was not significantly improved by SCS in this rather small study. The results suggest that SCS may reduce amputation levels in patients with severe inoperable leg ischaemia and be most effective in patients without arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(85 citation statements)
references
References 17 publications
2
78
1
3
Order By: Relevance
“…As judged by a visual analogue scale, pain relief was significantly better in the SCS group after 3 months (P < 0·001) 37 and 12 months (P < 0·01) 23 . In one study 38 , a highly significant reduction in pain score (from a mean of 50 to 25) was found during follow-up, but no difference between the two treatment groups.…”
Section: Pain Reliefmentioning
confidence: 93%
“…As judged by a visual analogue scale, pain relief was significantly better in the SCS group after 3 months (P < 0·001) 37 and 12 months (P < 0·01) 23 . In one study 38 , a highly significant reduction in pain score (from a mean of 50 to 25) was found during follow-up, but no difference between the two treatment groups.…”
Section: Pain Reliefmentioning
confidence: 93%
“…At a mean follow-up of 19 months, there was no significant difference in pain score improvement between the two groups. Conversely, from a similar study in which 51 patients were randomized to receive either oral medication alone or SCS with oral medication, Jivegård et al 72 reported a significant improvement in pain scores of the SCS-treated group, compared with the non-SCS group (p Ͻ 0.01).…”
Section: Chronic Critical Limb Ischemia and Painmentioning
confidence: 96%
“…Исследования эффективности спинальной нейростимуляции у пациентов с критической ишемией нижних конечностей, проблемы и перспективы применения К настоящему времени в мире выполнено 6 рандо-мизированных клинических [57][58][59][60][61][62] и 1 нерандомизи-рованное исследований [55] по сравнению спинальной нейростимуляции и консервативной терапии в лечении пациентов с критической ишемией нижних конечнос-тей, а также ряд когортных исследований, в которых рассматривалось течение заболевания у пациентов с имплантированной системой SCS (таблица). В боль-шинстве из них выявлено, что спинальная нейрости-муляция улучшает клиническое течение заболевания у пациентов с КИНК, в том числе приводит к меньшему числу ампутаций, в большей степени снижает боле-вой синдром и восстанавливает большее количество пациентов до II стадии по Фонтейну -Покровскому в…”
Section: отбор пациентов для имплантации системы спинальной нейростимunclassified